2013
DOI: 10.1590/s0100-204x2013001000001
|View full text |Cite
|
Sign up to set email alerts
|

Dietas artificiais para a criação de larvas e adultos da mosca-das-frutas sul-americana

Abstract: Resumo -O objetivo deste trabalho foi adequar as dietas artificiais para o desenvolvimento dos estágios de larva e adulto da mosca-das-frutas sul-americana (Anastrepha fraterculus). Para o estágio larval, foram testadas as seguintes dietas: D1, original, com 10 g de ágar; D2, modificada, com 3,6 g de ágar; e, D3, modificada, com bagaço seco de cana-de-açúcar. Para os adultos, foram testadas quatro dietas: A, levedura de cerveja + mel (2:1); B, açúcar refinado + extrato de levedura + gérmen de trigo cru (3:1:1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 11 publications
2
48
0
2
Order By: Relevance
“…In relation to weight of the pupae of A. fraterculus, Nunes et al (2013) found similar values (15.3 mg) using the same artificial diet with pH 4.0. The greater weight and larger number of pupae may be related to a favorable condition for larval development at this pH level, as well as for the bacteria associated to its intestinal flora.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In relation to weight of the pupae of A. fraterculus, Nunes et al (2013) found similar values (15.3 mg) using the same artificial diet with pH 4.0. The greater weight and larger number of pupae may be related to a favorable condition for larval development at this pH level, as well as for the bacteria associated to its intestinal flora.…”
Section: Discussionsupporting
confidence: 58%
“…Adults of A. fraterculus were kept in plastic cages (57 × 39 × 37 cm). Water and solid diet, composed of refined sugar, wheat germ, and yeast at a ratio of 3:1:1 were offered (Nunes et al, 2013). Eggs were collected from screens placed on the cage sides and were transferred to Erlenmeyer-type glass containers (500 mL), where they remained for a 24 h aeration process.…”
Section: Fruit Flies Rearingmentioning
confidence: 99%
See 2 more Smart Citations
“…A diet (Bionis YE MF and NS) based on yeast, wheat germ, and fine sugar was offered at the ratio of 1:1:3, respectively. Water by capillarity was also offered in acrylic boxes of type Gerbox (11.5 by 11.5 by 3.5 cm) (Gerbox, J. Prolab Ltda, São José dos Pinhais, Paraná, Brazil) containing cotton used for Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) (Nunes et al 2013).…”
Section: Methodsmentioning
confidence: 99%